Explaining the quality of green bonds in China. (20th June 2023) - Lin, Jiun-Da
Abstract: China has become the leading country in promoting green finance, and it now has one of the largest green bond markets in the world. To solve the problem of greenwashing in the global green bond markets, several transnational non-state actors have constructed global green bond standards, such as the Climate Bonds Standard. However, not all Chinese green bond issuers comply with global green bond standards. Why do some Chinese green bond issuers comply with the global green bond standards, while others don't? By analyzing a unique dataset of Chinese green bonds between 2016 and 2018, this article finds that Chinese green bond issuers are more likely to choose a higher level of compliance with the Climate Bonds Standard when the issuers have more political connections and Western linkages. In contrast, issuers' level of compliance is lower when the domestic regulatory agency does not actively encourage compliance with global green bond standards. Meanwhile, the findings indicates that Western linkages can moderate the effect of regulation on firms' compliance. Graphical abstract: Image 1 Highlights: Encouragement from domestic regulatory agencies positively affects Chinese green bond issuers' compliance with global standards. Chinese green bond issuers with political connections or Western linkages tend to prioritize higher compliance with global green bond standards. Chinese green bond issuers that are central state-owned enterprises tend to choose a higher level of compliance with global green bond standards. Western linkages moderate the impact of domestic regulation on Chinese green bond issuers' compliance with global standards.